2017
DOI: 10.1017/rep.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

The Political Incorporation of Muslims in the United States: The Mobilizing Role of Religiosity in Islam

Abstract: Despite the overwhelming evidence to the contrary, popular perceptions in the United States, especially among political elites, continue to believe that religious Muslims oppose American democratic traditions and values. While many studies find positive relationships between mosque attendance and civic participation among U.S. Muslims, an empirical and theoretical puzzle continues to exist. What is missing is research that examines the relationships between the multi-dimensional concept of religiosity and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 46 publications
(110 reference statements)
1
24
0
Order By: Relevance
“…Another US study by Ayers and Hofstetter (2008), based on a national survey of 1,846 Muslims, concluded that Muslims’ religious commitment and resources (measured by their mosque attendance, prayers, and community volunteering) “was positively associated with increased political participation” (Idem 2008, 17–18). This is strongly supported by the findings of another recent US study, based on a survey of 1,410 Muslims: Muslims who were very involved in their mosque were more than 50% more likely to become politically active (e.g., attending community meeting or rally, write to political officials) than those who were not involved in their mosque (Dana, Wilcox-Archuleta, and Barret 2017, 189). Similarly, a Swiss study among Muslims of Turkish, Maghreb, and former Yugoslavian background found that Muslims’ active involvement in religious associations (but not in ethnic organizations) has a significantly positive effect on their political participation (Giugni, Michel, and Gianni 2014).…”
Section: Synthesising Evidence: Relationship Between Islamic Religiossupporting
confidence: 57%
See 3 more Smart Citations
“…Another US study by Ayers and Hofstetter (2008), based on a national survey of 1,846 Muslims, concluded that Muslims’ religious commitment and resources (measured by their mosque attendance, prayers, and community volunteering) “was positively associated with increased political participation” (Idem 2008, 17–18). This is strongly supported by the findings of another recent US study, based on a survey of 1,410 Muslims: Muslims who were very involved in their mosque were more than 50% more likely to become politically active (e.g., attending community meeting or rally, write to political officials) than those who were not involved in their mosque (Dana, Wilcox-Archuleta, and Barret 2017, 189). Similarly, a Swiss study among Muslims of Turkish, Maghreb, and former Yugoslavian background found that Muslims’ active involvement in religious associations (but not in ethnic organizations) has a significantly positive effect on their political participation (Giugni, Michel, and Gianni 2014).…”
Section: Synthesising Evidence: Relationship Between Islamic Religiossupporting
confidence: 57%
“…2016; Read 2015) have consistently shown that Muslims who regularly attend and are active within mosques are significantly more likely to be also engaged in other non-Muslim civil society groups. In addition, this organizational facet of their religiosity has often been linked to increased political activism and trust (Fleischmann, Martinovic, and Böhm 2016; McAndrew and Sobolewska 2015; Ayers and Hofstetter 2008; Dana, Wilcox-Archuleta, and Barret 2017). These civically mobilizing effects can be considered well established in research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflecting on their behavior over the past 12 months, respondents across the board self-reported that they had avoided interactions with members of other groups, avoided interactions with members of other political parties, limited their posts on social media, and less frequently visited public places (such as restaurants, shopping malls, and parks) more than once in a while (see Table A.10). In line with the scholarship on foreign and American Muslims, we also explore how religiosity (Barreto and Bozonelos 2009; Barreto and Dana 2008; Dana, Barreto, and Oskooii 2011; Dana, Wilcox-Archuleta, and Barreto 2017; Jamal 2005; Oskooii and Dana 2018) and linked fate (Barreto and Bozonelos 2009; Barreto, Masuoka, and Sanchez 2008) affected self-reported avoidance shifts in behavior. 18 Similar to other studies, we find that more religious respondents and those with high linked fate are more insulated; they were significantly more likely than their counterparts to report avoidance behaviors (see Figure A.7).…”
Section: Survey Of Muslim Americansmentioning
confidence: 92%